An Epistemological Critique By Syed Naquid Al-Attas on The Relativism of Truth in Thomas Kuhn`s Paradigm - Sabilillah, Muhammad; Ramadhani, Mulyo Rizky (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This article examines the epistemological critique advanced by Syed Muhammad Naquib al-Attas against the concept of truth relativism inherent in Thomas Kuhn's theory of scientific paradigms. This study uses a library research method with a qualitative approach that is descriptive-analytical and comparative. According to Kuhn, scientific truth is relative to the paradigm adhered to by a scientific community, which encompasses a set of beliefs, values, and methods. As paradigms can shift through scientific revolutions, truth consequently becomes non-absolute and subject to change. In contrast, Syed Naquib al-Attas proposes an epistemology rooted in the Islamic tradition, wherein truth is considered absolute, objective, and derived from divine revelation. Al-Attas criticizes Kuhn's relativism because it disregards the metaphysical dimension of truth and potentially undermines the moral foundations and ultimate purpose of science. This study highlights the fundamental dichotomy between the secular-relativistic modern Western epistemology and an Islamic epistemology that upholds transcendent truth. As a solution, al-Attas proposes the project of the "Islamization of contemporary knowledge," a process of purifying knowledge by removing its secular, dualistic, and relativistic elements. Its ultimate aim is to restore science to its original function as a means to recognize the ultimate Truth (al-Haqq) and to serve God. Thus, the Islamization of knowledge is not merely a critique but a constructive proposal to the edifice of modern epistemology, which is perceived to have lost its spiritual and ethical compass.